Stabilization of Urate Oxidase Using Deep Eutectic Solvents Comprising Sucrose, Fructose, and Glycerol via Molecular Dynamics Simulation (Development Engineering Conferences Center Articles Database, 2025)
Serum uric acid levels are commonly assessed in human and other mammalian studies. Given the evolutionary loss of the gene encoding uricase in these species, elevated uric acid levels may lead to conditions such as tumor lysis syndrome, gout, and renal disorders. Consequently, the stability of this enzyme has garnered significant interest among researchers. Among various stabilization methods, the utilization of natural deep eutectic solvents (DESs) has been favored due to their numerous advantages over alternative approaches. In this study, DES was synthesized using three components: fructose, sucrose, and glycerol. Recombinant uricase (rasburicase) was produced in the BL21 bacterial strain, followed by protein purification using a nickel-affinity column. The optimal solvent concentration for the corresponding enzyme was determined, and molecular dynamics simulations were performed at this optimal concentration over a duration of 35 nanoseconds using GROMACS software. Analyses of RMSD, RMSF, SASA, and Rg were conducted, revealing reductions in these values, which correlate with decreased structural fluctuations and enhanced structural compactness. Additionally, analyses of RDF, total energy (sum of electrostatic and Lennard-Jones interactions), and number of contacts  for each eutectic component were calculated, with sucrose exhibiting the highest values relative to the other components. Overall, molecular dynamics simulation results indicated an increase in enzyme stability in the presence of the eutectic compared to the free enzyme.